Constructing the FCM model of the agile NPD process with a genetic algorithm: the case of Iranian companies. (29th July 2009) - Fekri, R.; Alizadeh, S.
The agile New Product Development (NPD) process is a complex and integrated process wherein all of its main factors have cause-and-effect relationships. A Fuzzy Cognitive Map (FCM) can be successfully applied to show the cause-and-effect relationships between the essential components in this kind of system and help managers extract a good view of this process and improve their decision quality. In this paper, an FCM model constructed with a Genetic Algorithm (GA) is proposed based on the interviews of NPD project managers in Iranian companies. The efficiency of the proposed model is compared with the FCM model constructed with a distance-based algorithm. The results shows that using a GA to construct the FCM model of the agile NPD process in Iranian companies is the better model compared to using a distance-based algorithm to construct the FCM model of this kind of process.